TINJAUAN YURIDIS PELANGGARAN HUKUM YANG DILAKUKAN OLEH WARGA NEGARA ASING YANG BERADA DI WILAYAH NKRI - Mardiyati, Siti (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Refugees leave their places of origin for a variety of reasons, mainly because of things that could endanger their lives during their stay, such as war or persecution. Nor do they get protection from their own country, and their own government often threatens to persecute them. This research uses normative juridic methods. The forms of violations committed by foreign nationals as refugees in the RI Territory include illegal entry into the territory of Indonesia, fighting, rape, and destruction of refugee facilities. Then the cause of the violations of the law committed by foreign nationals as refugees in the RI Territory is the difference of national rules, culture, customs and customs in Indonesia and in the country of origin. Another reason why refugees and asylum-seekers roam to commit violations is the lack of immigration detention facilities in Indonesia. The Indonesian government has established special rules on the conduct of refugees and asylum-seekers in its territory, so as not to disregard the behaviour of the refugee and asylees